Reservoir Characteristics and Sensitivity Evaluation of Chang 9 in the Southern Wangwazi Area of Wuqi Oilfield - Su, Yangbing (Scientific Journal of Technology, 2026)
To clarify the geological characteristics and sensitivity laws of the Chang 9 reservoir in the Wangwazi South area of the Wuqi Oilfield and to facilitate efficient development of the block, this paper conducts research by comprehensively applying methods such as core observation, thin section identification, mercury injection experiments, and sensitivity flow experiments. The results show that the study area is located on the western edge of the Yishan Slope in the Ordos Basin. The Chang 9 oil layer group reservoir is mainly composed of gray and dark gray fine-grained lithic feldspar sandstone, followed by feldspar lithic sandstone. The porosity is concentrated in the range of 1% to 5%, and the permeability is distributed between 0.05 and 0.4 mD, belonging to a very low porosity and tight reservoir. The pore types are mainly feldspar dissolution pores and intergranular pores, presenting a small pore and fine throat structure. The sensitivity evaluation shows that the reservoir has moderate to weak speed sensitivity (critical flow rate 3.72 m/D), moderate to weak water sensitivity, moderate to weak salt sensitivity (critical salinity 21.51 g/L), weak acid sensitivity, and weak to moderate to weak alkali sensitivity (critical pH value 11). Clay mineral migration and precipitation are the main damage mechanisms. The research results clarify the core characteristics and damage laws of the reservoir, providing geological basis for the formulation of reservoir protection plans and the optimization of development technologies, and also enrich the theoretical research on the Chang 9 reservoir in the Yanchang Formation of the Ordos Basin.